2021
DOI: 10.1002/jcop.22647
|View full text |Cite
|
Sign up to set email alerts
|

Iranian psychosocial status during and after COVID‐19 outbreak mandatory quarantine: A cross‐sectional study

Abstract: Quarantine, one of the most effective protection measures, plays an essential role in preventing the spread of infectious diseases. The coronavirus 2019 (COVID‐19) pandemic, along with quarantine, can have devastating consequences for individuals' mental and social health. This study examined the psychosocial status of individuals during and after quarantine in the COVID‐19 pandemic. This cross‐sectional study was conducted on 714 individuals in the general population during (365) and 3 months after quarantine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Although it can improve mental health, psychological problems were only revealed during the outbreak. During the pandemic, the public experienced anxiety, stress, fear, uncertainty and insecurity [ 47 ], indicating the need for more psychological support among patients with stroke, who are considered a vulnerable population. Thus, the PAC phase helps in the early recognition of psychological problems and the provision of timely interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Although it can improve mental health, psychological problems were only revealed during the outbreak. During the pandemic, the public experienced anxiety, stress, fear, uncertainty and insecurity [ 47 ], indicating the need for more psychological support among patients with stroke, who are considered a vulnerable population. Thus, the PAC phase helps in the early recognition of psychological problems and the provision of timely interventions.…”
Section: Discussionmentioning
confidence: 99%
“…On March 11, 2020, the World Health Organization declared COVID-19 a pandemic ( Sahin et al, 2020 ). Certainly, the general public has experienced anxiety, stress, fear, uncertainty, and insecurity as a result of the COVID-19 pandemic ( Zakeri et al, 2021c , f ). In this dire situation, nursing is one of the most important occupational groups, as well as one of the foundations of healthcare organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Poland and the Philippines were the two countries with the highest levels of anxiety, depression, and stress 4 . Some studies have reported numerous mental disorders due to the prevalence of COVID‐19 disease and the effects of quarantine in the community 5 . In Iran, high levels of anxiety, stress, 6 and fear have been reported 7 …”
Section: Introductionmentioning
confidence: 99%
“…4 Some studies have reported numerous mental disorders due to the prevalence of COVID-19 disease and the effects of quarantine in the community. 5 In Iran, high levels of anxiety, stress, 6 and fear have been reported. 7 According to the World Health Organization (WHO) on April 27, 2020, 109 577 laboratory-confirmed COVID-19 incidents, which included 3809 deaths, were widely reported in China and 28 673 incidents in 104 other countries.…”
Section: Introductionmentioning
confidence: 99%